Neonatal Seizure and Afterward, Epilepsy: A Systematic Review - Zafari, Ali; Pajouhandeh, Fatemeh; Arab Ahmadi, Mehran (International Clinical Neuroscience Journal, 2019)
Background: The purpose of the current study is to estimate the incidence of epilepsy after neonatal seizure (NS) by reviewing of the latest studies on the relationship between NSs and epilepsy in newborns and also discuss risk factors may contribute to this relationship. Methods: A literature review was performed using the search terms “neonatal seizure AND epilepsy,” “newborns AND epilepsy,” “postneonatal epilepsy.” After exclusion of several studies, which did not meet inclusion criteria, the epilepsy incidence rate was measured by dividing the number of all cases of epilepsy who had a history of NS in selected studies considered with the number of all newborns enrolled to the studies minus the number of cases who lost the follow-ups. Results: By reviewing the literature, 13 studies were found, which completely meet the inclusion criteria and published between 2009 and 2019, of which three were population-based while the remaining studies performed hospital-based. Overall, the population evaluated in these series has been estimated to be 2438 newborns of which 454 died, and 300 missed the follow-ups. The incidence rate for afterward epilepsy in all 1684 subjects with NS was 20%, literally 343 of the NS subjects. Conclusion: The presented review enrolled the most recent studies encompassing enough and extended the time as well as adequate sample size. Epilepsy is considered a common outcome of NS, particularly in those with other neurodevelopmental comorbidities, even if there were always several limits associated with various study designs and condition.